-15z=24z+36

Simple and best practice solution for -15z=24z+36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15z=24z+36 equation:


Simplifying
-15z = 24z + 36

Reorder the terms:
-15z = 36 + 24z

Solving
-15z = 36 + 24z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-24z' to each side of the equation.
-15z + -24z = 36 + 24z + -24z

Combine like terms: -15z + -24z = -39z
-39z = 36 + 24z + -24z

Combine like terms: 24z + -24z = 0
-39z = 36 + 0
-39z = 36

Divide each side by '-39'.
z = -0.9230769231

Simplifying
z = -0.9230769231

See similar equations:

| Fx-gx=z | | 28x+27= | | 2((-8)-2)+8= | | 3x(2x+20)=4x-20 | | -9n+19=-8n-14 | | 6(9z-12)=9(5z+11) | | 2x+33?5x+6= | | 100x*10000=250x | | -6+4x+6x=-66 | | 4m-20=20-16m | | y=4x^3-.5x+2 | | 8c-120=240+5c | | 7x+8+4x=-80 | | x^4-20x^3+141x^2-406x+392*x-9=0 | | T(f+9)=40 | | 5y-7y=10 | | 6x-30=60-3x | | 9r-4=44+6r | | 5(2x+-7)-3(3x-10)+4= | | (D^3-D^2-4D-2)y=0 | | 46+16y=572 | | 4x-39=90 | | -17-20=-13x+80 | | 2x+3=9x+12-x | | 4x+2+6x=82 | | -5d+120=-6d-9 | | 8(3G+5R)= | | 14+29m=28+22m | | -8x-22=-3(x-1) | | 4x+17=90 | | 2f+20=101-f | | 2w-18w=-32 |

Equations solver categories